PENENTUAN POPULARITAS KPOP MENGGUNAKAN HASIL PENGHITUNGAN STATISTIK BERDASARKAN DATA PADA MEDIA SOSIAL TWITTER DENGAN KATA KUNCI UNIGRAM (Studi Kasus : @Koreaboo) - Sabilla Opi Aprilia, (2020)
Popularity is an achievement for everyone. The more people advocate something or claim that someone is liked by many people, the more attention it will get, the more popular a group or individual is considered. Just like any of the popular objects that are highly desirable to date is K-Pop. The use of social media in the provision of information can increase the popularity of K-Pop easier. In this study crawling data was done on @Koreaboo Twitter account. Data is processed using preprocessing methods, then the data is manually categorized into a document with three K-Pop groups (BTS, Exo & Twice) which is subsequently carried out the value of the values with TFIDF to search for a unigram keyword or context. Calculation results with the program about the many tweets that have been categorized as known keywords from 1587 tweets, the most value appears in the BTS category with an end result of 386 tweets with an average of 24.32262129% with an EXO yield of 122 tweets with an average of 7.68746061% and Twice 117 tweets averaged 7.37240075% based on Twitter accounts (@Koreaboo).